Control quimico de malezas en frijol (Phaseolus vulgaris L.) en el Estado de Veracruz - Esquivel, V.A.=700 1 Cano, O.; Lopez, E.
(En, Es)
ilus., 11 ref.
Keywords: PHASEOLUS VULGARIS; CONTROL QUIMICO; MALEZAS; HERBICIDAS; ALACLORO; LINURON; HUMEDAD RELATIVA; MEXICO; HUMEDAD RESIDUAL